AB0617 Bone involvement in systemic mastocytosis: cases review. (23rd January 2014) - García, M. L.; Blanco, J. M.; Gómez, C.; Torre, I.; Estopiñan, L.; Gorordo, J. M.; Pérez, C. E.; Ruíz, E.; Úcar, E.; Eva, G.; Fernandez, O.
Abstract : Background: Systemic mastocytosis is a clonal disease of mast cell progenitors in bone marrow which causes abnormal growth and accumulation of mast cells in skin and other organs. Bone involvement occurs in 70% of cases; sclerotic, lytic lesions, and osteoporosis have been described, but they are rare as a form of disease presentation. Objectives: To describe the main epidemiological and clinical features of systemic mastocytosis, focusing especially on bone involvement. Methods: We make a review of systemic mastocytosis patients diagnosed in our hospital (by Rheumatology, Allergy and Hematology departments) and describe the main epidemiological and clinical characteristics. Results: We found 5 cases of systemic mastocytosis diagnosed in a 22 year period. The study includes 3 women and 2 men, ages ranged 27 to 59 years. The delay of diagnosis from the onset of symptoms varies between 3 and 13 years. It presented with respiratory involvement in 2 cases, digestive in 1 case, skin in 1 case, and bone in only 1 case. 3 patients had allergic reactions in some stage of evolution, 3 skin symptoms, 3 patients had episodes of hypotension, dizziness, palpitations and syncope. Regarding to the musculoeskeletal system, 4 patients had bone involvement, 1 patient previously diagnosed with chronic osteomyelitis and 3 patients with osteoporosis and multiple vertebral collapses, one patient also had multiple rib fractures. The skeletal survey study showed 3 patients with lytic bone lesions and 2 patients with sclerotic lesions. Tryptase levels were elevated in 4 patients, whereas urine histamine levels were elevated in all 5 patients. Every patient had a bone marrow biopsy with diagnosis of systemic mastocytosis. Conclusions: Systemic mastocytosis is a rare disease in our environment, the diagnosis uses to be late and requires high index of suspicion. Osteoporosis secondary to mastocytosis is usually severe, and it is very rare as the first manifestation of the disease. Two of the cases reviewed in this series had been admitted to our department for vertebral compression fractures, and we made the diagnosis in one of them, a middle-aged man with no other cause of osteoporosis, with initial bone marrow aspirate apparently normal. It has been reported that up to 9% of cases of "idiopathic" male osteoporosis may be caused by mastocytosis. We believe that tryptase and histamine levels should be included in the lab exams in patients with osteoporosis and fractures after ruling out other common causes. References: References: Barete S, Assous N, de Gennes C, Grandpeix C, Feger F, Palmerini F, Dubreuil P, Arock M, Roux C, Launay JM, Fraitag S, Canioni D, Billemont B, Suarez F, Lanternier F, Lortholary O, Hermine O, Francès C. Systemic mastocytosis and bone involvement in a cohort of 75 patients. Ann Rheum Dis. 2010 Oct;69(10):1838-41. doi: 10.1136/ard.2009.124511. Epub 2010 Jun 22. Salles M. Holgado S. Navarro J.-T. Ribera J.-M. Riera E. Milla F. Tena X. Osteoporosis as a first manifestation of systemic mastocytosis. Study of 6 cases. Medicina Clinica. 128 (6) (pp 216-218), 2007. Date of Publication: 17 Feb 2007. Ediciones Doyma, S.L. Rosenbaum RC, Frieri M, Metcalfe DD. Patterns of skeletal scintigraphy and their relationship to plasma and urinary histamine levels in systemic mastocytosis. J Nucl Med 1984; 25:859. Disclosure of Interest: None Declared